Cytotoxicity and aryl hydrocarbon receptor-mediated activity of n-heterocyclic polycyclic aromatic hydrocarbons: structure-activity relationships - Sovadinová, Iva; Bláha, Luděk; Janošek, Jaroslav; Hilscherová, Klára; Giesy, John P; Jones, Paul D; Holoubek, Ivan (Environmental toxicology and chemistry, 2006)
Toxic effects of many persistent organic pollutants (e.g., polychlorinated biphenyls or polychlorinated dibenzo-p-dioxins and furans) are mediated via the aryl hydrocarbon receptor (AhR). Although polycyclic aromatic hydrocarbons (PAHs) and their derivatives also activate AhR, their toxic effects remain to be fully elucidated. In the present study, we used the in vitro H4IIE-luc transactivation cell assay to investigate cytotoxicity and potencies to activate AhR by 29 individual PAHs and their N-heterocyclic derivatives (aza-PAHs). The aza-PAHs were found to be significantly more cytotoxic and more potent inducers of AhR than their unsubstituted analogues. Several aza-PAHs, such as dibenz[a,h]acridine or dibenz[a,i]acridine, activated AhR within picomolar concentrations, comparable to the effects of reference 2,3,7,8-tetrachlorodibenzo-p-dioxin. Ellipsoidal volume, molar refractivity, and molecular size were the most important descriptors derived from the modeling of quantitative structure-activity relationships for potencies to activate AhR. Comparable relative toxic potencies (induction equivalency factors) for individual aza-PAHs are derived, and their use for evaluation of complex contaminated samples is discussed.
Keywords: biotest; financování organizované; Animals; kvantitativní vztahy mezi strukturou a aktivitou; Cell Line, Tumor; Quantitative Structure-Activity Relationship; Molecular Structure; nádorové buněčné linie; receptory aromatických uhlovodíků; Heterocyclic Compounds; heterocyklické sloučeniny; Financing, Organized; regulace genové exprese; molekulární struktura; Receptors, Aryl Hydrocarbon; polycyklické aromatické uhlovodíky; Polycyclic Aromatic Hydrocarbons; Biological Assay; krysa rodu Rattus; Gene Expression Regulation; zvířata; Rats; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions